Scale Construction to Measure the Attitude of Hilly Tribes towards Environmental Conservation - Sasmitha, R; Muhammed Iqshanullah, A; Arunachalam, R; Shanjeevika, A (Indian Journal of Extension Education, 2021)
To develop and standardize a scale to measure tribes’ attitude towards environmental conservation â€œEqualÂ Appearing Intervalâ€ method was used. Possible items concerning the psychological object i.e. Environmental Conservation were collected. 42 judges responded their opinion. Finally on the basis of scale value and Q value 15 statements constituted scale. Items having high scale values with the corresponding Q values were selected from each compartment. The reliability (r 0.647) of the scale was determined by â€˜Split-halfâ€™ methodÂ and administered in a non-sample area. Further, the whole test reliability (rtt) was computed using theÂ Spearman-Brown Prophecy formula and it was found to be 0.753 which is reliable. Content validation wasÂ carried out by subjecting the 15 items to judges’ opinion on a four point continuum. The overall mean score of the scale was worked out as 3.19. The standardized scale would have practical applicability in discovering the intensity of attitude of tribes and thus it facilitates to take right decisions by policy makers.